LEARNING PHRASEOLOGY IN TAJIK SCHOOLS IN UZBEKISTAN - Nurulloev Jahongir (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the construction, spelling, and use of grammatical and grammatical expressions in Tajik schools in Uzbekistan. At the same time, opinions are expressed on the basis of secondary school textbooks.